Addressing sexual health needs: a comparison of a one-stop shop with separate genitourinary medicine and family planning services. Issue 4 (1st October 2010) - French, Rebecca S; Mercer, Catherine H; Robinson, Angela J; Gerressu, Makeda; Rogstad, Karen E; ,
Abstract : Background and methodology: Little evidence is available on the extent to which one-stop shops address users' sexual health needs and the extent to which they identify additional needs users may not have identified. As part of the One-Stop Shop Evaluation, a questionnaire was designed to compare the reasons for users' visits and the reported outcomes of visits at a one-stop shop with the experiences of users in separate genitourinary medicine (GUM) and contraceptive clinics. Results: The difference in the proportions of those attending the one-stop shop and those attending the control sites services for a sexually transmitted infection (STI)-related reason who were diagnosed with an STI was minimal, but those attending for an STI-related reason in the one-stop shop were more likely to receive an additional contraceptive outcome. Women attending for a contraceptive-related reason at the one-stop shop were more likely to have an STI screen than those attending the control sites for the same reason, but there was little difference in the proportions amongst this group receiving an STI diagnosis or receiving treatment. When focusing on women attending for a pregnancy-related reason, one-stop shop users were more likely to have received contraceptive advice or supplies. Discussion and conclusions: It was not possible in our evaluation to determine the relative effectiveness of the one-stop shop in comparison to the traditional GUM and contraceptive clinics in improving sexual health status, however the one-stop shop was more likely to address additional sexual health needs that service users may not have previously identified.